Applying the trans‐contextual model to promote sport injury prevention behaviors among secondary school students. (6th July 2021) - Lee, Alfred S. Y.; Standage, Martyn; Hagger, Martin S.; Chan, Derwin K. C.
Abstract : The current study tested the effects of an intervention based on the trans‐contextual model (TCM) on secondary school PE students' sport injury prevention behavior and on theory‐based motivational and social cognition mediators. Participants were PE students ( N  = 1168; M age  = 13.322 ± 1.045, range = 12–16; female = 51.721%) who participated in a 3‐month cluster‐randomized controlled trial. Schools were randomly assigned to a treatment group, in which PE teachers received training to be more supportive of psychological needs in teaching sport injury prevention, or a control group, in which PE teachers received no training. Participants completed survey measures of TCM variables and self‐reported sport injury prevention behavior at baseline and at 3‐month post‐intervention follow‐up. The proposed TCM model exhibited adequate fit with the data, χ 2  = 143.080 (df = 19), CFI = 0.956, TLI = 0.916, RMSEA = 0.078 (90% CI = 0.066–0.090), and SRMR = 0.058. We found positive, statistically significant direct intervention effects on changes in perceived psychological need support (β = 0.064, p  = 0.020). We also found positive, significant direct (β = 0.086–0.599, p  < 0.001) and indirect (β = 0.002–0.027, p  = 0.020–0.032) intervention effects on changes in TCM variables and behaviors to prevent sport injuries. Our findings support the TCM as a useful framework for building an intervention for promoting sport injury prevention behaviors among secondary school students.